Method for weak zones location at the coal-bed – host rock joint relative to the problem of sudden outbursts: theory and laboratory experiment (Fracture and Structural Integrity, 2022)
Within the framework of a geomechanical model that describes the deformation of a rock mass during the subhorizontal coal-bed extraction, the mechanism for the formation and implementation of a sudden outburst is substantiated: as working face gets close to the weak zone of coal-bed – host rock joint, areas of tensile stresses arise, which creates the prerequisites for face space spalling and coal loss with methane. The inverse problem of determining the conditions at the horizontal boundaries of a coal-bed is formulated and solved using tomography data (longitudinal wave velocity V distribution) and the empirical dependence of V on the mean normal stress σ.Lab tests results on stepwise compression of parallelepipeds made of artificial geomaterials are presented. Tomography of the specimens was performed by acoustic sounding data, and the distribution of velocities V* was found. Using the pre-established empirical dependence V(σ) for geomaterial, the distribution σ*=V-1(V*) in the specimen was calculated, which served as input data for inverse problem of determining the shear stresses σxy at the “specimen faces – press platens” joints. Lab data inversion confirmed the possibility of identifying weak zones of the boundaries where σxy=0. These zones are associated with probable nucleus of failure and sudden outbursts.
Keywords: coal-rock mass; lab test; tomography; geomaterial; inverse problem; sudden outburst